2011
DOI: 10.1063/1.3609068
|View full text |Cite
|
Sign up to set email alerts
|

Nanojunctions in conducting polypyrrole single nanowire made by focused electron beam: Charge transport characteristics

Abstract: A focused electron (E)-beam with various doses was irradiated on the intended positions of conducting polypyrrole (PPy) single nanowire (NW) to fabricate nanojunctions. The current-voltage characteristics and their temperature dependence of the PPy single NW with nanojunctions were measured and analyzed. By increasing the E-beam dose and the number of nanojunctions, the current level of the single NW was dramatically decreased, and the conductance gap became more severe as the temperature decreased. The charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Then, they investigated the charge transport characteristics of the irradiated polypyrrole and claimed that the nanojunctions made by focused EB acted as a quasi-potential barrier for charge conduction, which inhibited charge hopping. 16 Ranganathaiah et al 17 revealed that 8 MeV EB irradiation can cause both chain scission and cross-linking in polymerbased Bakelite RPC detector material. In low irradiation dosages (20−40 kGy), the scission of hydrogen bonded phenolic groups caused the formation of OH − and H + free radicals and boosted σ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, they investigated the charge transport characteristics of the irradiated polypyrrole and claimed that the nanojunctions made by focused EB acted as a quasi-potential barrier for charge conduction, which inhibited charge hopping. 16 Ranganathaiah et al 17 revealed that 8 MeV EB irradiation can cause both chain scission and cross-linking in polymerbased Bakelite RPC detector material. In low irradiation dosages (20−40 kGy), the scission of hydrogen bonded phenolic groups caused the formation of OH − and H + free radicals and boosted σ.…”
Section: Introductionmentioning
confidence: 99%
“…However, Joo et al found that in focused EB (300 keV to 2 MeV, 8.0 × 10 16 electrons/cm 2 ) irradiated polypyrrole single nanowire, with increasing EB dosage, the interaction between EB and the electron-rich C–N groups in the pyrrole ring caused polymer chain distortion, which reduced coplanarity of the aromatic ring and shortened the π-conjugation length, and hence reduced σ. Then, they investigated the charge transport characteristics of the irradiated polypyrrole and claimed that the nanojunctions made by focused EB acted as a quasi-potential barrier for charge conduction, which inhibited charge hopping . Ranganathaiah et al revealed that 8 MeV EB irradiation can cause both chain scission and cross-linking in polymer-based Bakelite RPC detector material.…”
Section: Introductionmentioning
confidence: 99%